The The Influence of Organizational Culture on Employee Performance with Organizational Commitment as an Intervening Variable - Saebah, Nur; Merthayasa, Alit (Ridwan Institute, 2024)
Organizational culture encompasses the values, norms, and beliefs shared by organizational members and can play a crucial role in shaping individual behavior and performance. In a competitive business environment, a deep understanding of the relationship between organizational culture, organizational commitment, and employee performance is key to achieving competitive advantage. This study examined organizational culture's effect on employee performance with organizational commitment as a mediating variable. This study uses quantitative research methods with a survey approach. Research data were collected using a questionnaire. The data that has been collected is then statistically analyzed with the help of the SPSS program. The results showed that organizational culture positively and significantly affects employee performance through organizational commitment. Therefore, organizations need to create an organizational culture that supports employee performance.